Die Befugten zur Durchführung von Steuerfahndung. Staatliche Behörden der Ukraine - Petrova, Iryna Pavlivna (Ostinstitut Wismar, 2024)
The article explores the current state and structure of Ukraine’s tax system, highlighting key reforms and the legal framework for tax administration, including classifications of taxes under Ukrainian law. It provides an analytical overview of tax audits, their legal basis, and regulatory procedures as defined by current legislation. Particular focus is given to the authorities responsible for conducting financial and tax-related investigations, with emphasis on the Bureau of Economic Security as the central institution overseeing the use of financial aid provided by Ukraine’s Western partners. The article examines the Bureau’s formation, organizational structure, core functions, investigative jurisdiction, and legal competencies in conducting financial investigations. Furthermore, the study identifies critical challenges and institutional issues faced by the Bureau in the broader context of Ukraine’s alignment with European standards and its path toward European integration. This work aims to inform legal scholars, practitioners, and international stakeholders about Ukraine’s evolving mechanisms for addressing financial crime within a European legal and institutional framework.

У статті досліджується поточний стан та структура податкової системи України, висвітлюються ключові реформи та правові засади адміністрування податків, включаючи класифікацію податків згідно з українським законодавством. Стаття містить аналітичний огляд податкових перевірок, їх правової бази та регуляторних процедур, визначених чинним законодавством. Особлива увага приділяється органам, відповідальним за проведення фінансових та податкових розслідувань, з акцентом на Бюро економічної безпеки як центральній установі, що здійснює нагляд за використанням фінансової допомоги, наданої західними партнерами України. У статті розглядається створення Бюро, його організаційна структура, основні функції, підслідність та правові повноваження у проведенні фінансових розслідувань. Крім того, дослідження визначає критичні виклики та інституційні проблеми, з якими стикається Бюро в більш широкому контексті наближення України до європейських стандартів та її шляху до європейської інтеграції. Ця робота має на меті поінформувати науковців, практиків та міжнародні зацікавлені сторони про механізми боротьби з фінансовими злочинами, що розвиваються в Україні в рамках європейської правової та інституційної системи.
Ukrainian State Authorities Empowered to Conduct Financial (Tax) Investigations
Keywords: Combating Financial Crime; the Bureau of Economic Security; Jurisdiction over crimes; Tax Offenses; European Integration; боротьба з фінансовою злочинністю; бюро економічної безпеки; підслідність; податкові злочини; Європейська інтеграція